Externalised Haptic of a Tilted Scleral-fixated Intraocular Lens: A Case Report - Parthiban, Priyadarshini; Ezhilvathani, T. N. (Nepalese Journal of Ophthalmology, 2025)
Introduction: Implantation of scleral-fixated intraocular lens (SFIOL) has become a common technique done in the recent times when there is inadequate support of the posterior capsular bag. As this technique of SFIOL implantation needs good expertise when performed, if not done properly it may result in several post-operative complications which may require a re-surgery that delays the patient’s visual recovery. One such post-operative complication is haptic exposure in the post-operative period which is reported in this case report. This case report stresses on the importance of correct surgical technique and frequent post-operative follow up when SFIOL is implanted. Case: A 66-year-old female presented to OPD with complaints of diminution of vision in both eyes for the past six months following cataract surgery which was done elsewhere in some other hospital a year ago. Observation: On slit lamp examination, an externalised haptic of a tilted SFIOL was noted in the subconjunctival space of patient’s left eye. Conclusion: Continuous professional development and adherence to best practice guidelines are imperative for optimising the success of SFIOL procedures.